Adhesion on Olympus Castable Ceramics (OCC) - Akagawa, Susumu; Tawada, Yasuyuki; Iijima, Hiroshi; Mogi, Mitsuru; Maeda, Toshio; Murata, Yoko; Hata, Yoshiaki (Nihon Hotetsu Shika Gakkai Zasshi, 1997)
SiO2 type glass ceramics (OCC), which educe mica and -spodiumen crystals, were developed in the 1980 s and clinically applied in 1986. On a commercial basis, some of the clinical failure cases developed, and since 1995, properties of the material and technique have been reexamined. OCC restorations are now cemented by Panavia 21, a luting agent. Some of the main improvements of OCC to prevent failure are as follows: Currently used pellet type was changed to powder type and stabilization of the material was attempted. In the laboratory technique, polishing of OCC restorations, which has been done after ceraming, was done before ceraming, in the state of as-cast because processed micro cracks became obtuse angles or diminished. The crystalization schedule was examined, and a modified schedule was found to be useful for obtaining small, constant sized crystal grains. Furthermore, applications of OCC to the artificial denture teeth or implant prosthesis and so on were discussed.